The mattering of African contemporary art: value and valuation from the studio to the collection - Gurney, Kim Janette (Department of Environmental and Geographical Science, 2019)
This interdisciplinary research bridging geography and fine art (‘geo-aesthetics’) follows contemporary artwork journeys from the studio into the public domain to discover how notions of value shift as the artwork travels. It seeks transfigurative nodes and their catalysts to explore how art matters: firstly how it becomes matter in the studio, and then how it comes to matter beyond the studio door. Two case studies at key moments of revaluation, a buy-out and a buy-in, both reveal responses to uncertainty that stress different kinds of collectivity. The first case study follows artistic practice and process in four studios in a Johannesburg atelier to investigate intrinsic value and finds ‘artistic thinking’. The second case study follows the assemblage of a private art collection managed from Cape Town, initially as an art fund, to investigate extrinsic valuation and finds ‘structural thinking’. These different modalities in the production and consumption circuitry of the artworld have unexpected correlations including shared artists and three linking concepts, namely, uncertainty, mobility, and the web. These in turn inform three observations: nested capacity, derivative value, and art as a public good. Two key findings emerge: contemporary art is itself a vector of value that performs meaning as it moves; and public interest is a central characteristic from which other valuations flow. The research uses repeat interviews, site visits and visual methods, which are triangulated with artwork trajectories to surface linkages between space and imagination. It offers a performative theory of value that speaks to an expanded new materialism. Applying an ecological framework allows a final transfiguration for an artworld ecosystem that (re)values contemporary art as part of an undercommons.